Enhancement of Fibrinolytic and Thrombolytic Potential in the Rat by Treatment with an Anabolic Steroid, Furazabol - Kumada, Toshihiko; Abiko, Yasushi (Thrombosis and Haemostasis, 1976)
The effect of long-term ingestion of an anabolic steroid, furazaboi, was studied on coagulo-fibrinolytic systems in the rat.During the administration of furazabol at the daily dose of 0.04, 0.2 or 1 mg/rat for 3 months, the most remarkable changes were increase in the plasminogen activator activity in blood and the lung tissue and decrease in plasma fibrinogen level as well as decrease in plasma cholesterol. It was a very important finding that in most of the rats the furazabol treatment was effective in reducing susceptibility to lactic acidosis-induced pulmonary thrombosis. No meaningful changes were observed in other parameters tested including ADP-induced platelet aggregability, plasma recalcification time, plasma plasminogen, plasma antiplasmin activity, plasminogen activator content of tissues other than the lungs and the release of vascular activator induced by venous occlusion. One month after cessation of the furazabol treatment, these altered parameters tended to return to normal.Independently on the furazabol treatment, highly significant positive correlation existed between the plasma activator activity and the pulmonary tissue activator content. This indicated that the major source of plasma activator in the rat was the lung tissue and that the furazabol treatment increased the circulating activator activity through enhancing activator content in the lungs.